Public Diplomacy of Indonesia Towards Turkey Through The Youtube Platform Endonezya Evi - Fitria Afriyanti; Wawan B. Dermawan; Deasy S. Sari (Green Publisher Indonesia, 2024)
Globalization brings changes to all fields including the practice of state public diplomacy, changes occur in public diplomacy media that use social media, one of which is YouTube used by Indonesia through the Endonezya Evi Platform in Turkey, this change occurs because the use of conventional media previously used by Indonesia through the Indonesian Cultural House has shown a decline in Turkish public attention so that new media is needed that is more easily accepted by the Turkish public. Evi's Endonezya platform was deemed easier to access and did not require a large amount of money to run. <The purpose of this article is to find out whether the Endonezya Evi Platform can be used in the practice of Indonesian public diplomacy in Turkey and how it impacts. <The method used in this article is descriptive analysis by examining the Endonezya Evi Platform used by Indonesia. This article shows that the Endonezya Evi Platform is a new media that can be used in the practice of Indonesian public diplomacy because it can reach a large audience and does not require large costs and the Endonezya Evi Platform fulfills the components of public diplomacy so that it can be used as a tool in the practice of Indonesian public diplomacy in Turkey.